Faktor-faktor penentu ketidakpatuhan cukai di kalangan individu berpendapatan tinggi di Malaysia - Jaffar, Tukiran (2022)
The importance of taxpayers who are categorized as High Net Worth Individuals (HNWI) in generating national income is undeniable. Although the number of HNWI in Malaysia is small, the income tax revenue contributed by this group is high. Nevertheless, statistical evidence shows that the Inland Revenue Board of Malaysia (IRBM) is facing problem of tax noncompliance among HNWI. Tax non-compliance among this group will not only reduce government revenue collection which will affect the country's planning on development and management, but also affect the quality of life of the people, especially for the low-income group in an unbalanced economic environment. Despite its importance, little has been focused on the issue of tax non-compliance among HNWI. Therefore, this study takes the initiative to empirically investigate the factors that contribute to tax non-compliance among HNWI. This study applies Deterence Theory to determine whether factors such as tax rates, penalty rates, sources of income and the appointment of taxation practitioners have a relationship with tax non-compliance among HNWI in Malaysia. In this study, actual data from HNWI in Malaysia that were audited by IRBM for the year of assessment 2019 were used. Multiple regression techniques were used to analyse the data. The findings revealed that only the tax rate has no relationship, whereas the penalty rate, source of income, and appointment of taxation practitioners all have a relationship in influencing tax noncompliance among Malaysian HNWI. These findings have important implications for academics and the government, particularly IRBM, in developing the best strategy for designing an effective and efficient tax compliance programme among Malaysia's HNWI.